Kajian Literatur Instalasi Listrik pada Bangunan Cerdas Berbasis IoT untuk Efisiensi Energi - Mochamad Levi Adilah; I Nyoman Satya Kumara; I Wayan Sukerayasa; I Made Arsa Suyadnya (Lembaga Pengembangan Kinerja Dosen, 2026)
Electrical installations in smart buildings have evolved significantly from conventional systems to Internet of Things (IoT)-based systems that emphasize energy efficiency, adaptability, and environmental sustainability. This study reviews literature from the past six years in Indonesia, focusing on aspects of installation design, monitoring systems, automation, and the application of sensor and microcontroller technologies to achieve energy efficiency. Various studies indicate that the implementation of IoT in electrical systems enables real-time monitoring of power consumption, automatic load control, and integration with centralized energy management systems. This technology not only enhances user comfort but also reduces operational costs and supports energy sustainability through electricity savings of up to 50%. Moreover, the use of wireless networks and smart sensors in modern buildings can identify abnormal energy consumption patterns and provide early warnings for potential failures or energy leakage. The implementation of such systems contributes to realizing the smart building concept that is efficient, safe, and environmentally oriented. Therefore, IoT-based electrical installations hold great potential for widespread application in supporting national energy efficiency initiatives and promoting sustainable development in the digital era.